Copyright Law Protection (Law No. 28 of 2014) in Encouraging the Creative Economy That has an Impact on Improving the Indonesian Economy - Hafied Noor Bagja; Nina Nurani (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2023)
Creative Economy is an economic activity that originates from the utilization of individual creativity, skills and talents in terms of creating prosperity and creating jobs by generating and exploiting individual creative and creative power. In the world of trade, the business sector in every business must have intellectual property in it, including products produced by the creative economy community which generally have a trademark. The development of science and technology requires normative support in order tobe a means of improving the creative economy, so that potential creators need adequate legal protection to be motivated to produce original creations. This study discusses the progressive protection of creators in encouraging the creative economy in Indonesia. The research method used is a qualitative approach, data collection methods through literature study, and qualitative normative data analysis techniques. The results of the study show that with the protection of copyright law, it can have a positive impact on the sustainability of the company and increase the income of human resources.